Formulation of Edible Film Preparation from Musk Orange Essential Oil (Citrus Microcarpa Bunge) in Inhibiting the Growth of Streptococcus mutans Bacteria and Candida Albicans sp Fungus - Anggraini, Chorry Dwi; Mayasari, Ulfayani (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the formulation of edible film preparations from musk orange essential oil (Citrus Microcarpa Bunge) in inhibiting the growth of Streptococcus mutans and Candida Albicans sp. Fungus. The data collection technique uses laboratory-based experimental testing. Musk lime plants were taxonomically identified at the Herbarium Medanase (MEDA) laboratory, USU Campus, Medan, then processed using the steam distillation method to produce essential oils. The essential oil activity test uses concentrations (1%, 2%, 3%, 4% and 5%) to test its antibacterial and antifungal activity. Musk orange essential oil made in the form of an edible film was then tested for its physical properties as well as antibacterial and antifungal activity against the fungi S. mutans and C. albicans. The yield of essential oils was 0.93539gr/ml from 15kg of 8.5ml sample. The test results of the edible film preparation of the essential oil of musk orange have a distinctive aroma of fresh menthol and musk orange, orange color, smooth texture, sweet taste. Testing the ability of edible film preparations from essential oils has the highest inhibition zone results at a concentration of 4%, 5% which has natural antimicrobial substances. The yield of essential oils was 0.93539gr/ml from 15kg of 8.5ml sample. Essential oil activity tests produced the highest inhibition zones in bacteria and fungi at concentrations of 4% and 5%. The test results of the edible film preparation of the essential oil of musk orange have a distinctive aroma of fresh menthol and musk orange, orange color, smooth texture, sweet taste. Testing the ability of edible film preparations from essential oils has the highest inhibition zone results at a concentration of 4%, 5% which has natural antimicrobial substances.